62.5k views
5 votes
Factor 1-2sin^2(x)+sin^4(x)

1 Answer

7 votes

Answer:


\left(1 - \sin^(2)(x)\right)^(2).

Explanation:

Notice that "
1" is equal to "
1^(2)" whereas
\sin^(4)(x) = {\left(\sin^(2)(x)\right)}^(2). Therefore:


\begin{aligned} & 1 - 2\, \sin^(2)(x) + \sin^(4)(x) \\ =\; & 1^(2) - 2\, \sin^(2)(x) + {\left(\sin^(2)(x)\right)}^(2)\end{aligned}.

Make use of the identity
(a - b)^(2) = a^(2) - 2\, a\, b + b^(2). In this case, set
a = 1 whereas
b = \sin^(2)(x). Therefore:


\begin{aligned} & 1^(2) - 2\, \sin^(2)(x) + {\left(\sin^(2)(x)\right)}^(2) \\ =\; & a^(2) - 2\, a\, b + b^(2) \\ =\; & (a - b)^(2) \\ =\; & {\left(1 - \sin^(2)(x)\right)}^(2)\end{aligned}.

User David Goodwin
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.